Curable composition for producing transparent orthodontic accessories
By developing a curable composition containing specific chemical components and nanofiller particles, the problem of orthodontic attachments visible on the tooth surface in orthodontic therapy is solved, and the production of orthodontic attachments with high transparency, aesthetics and good mechanical properties is achieved.
Patent Information
- Application Number
- CN202380055072.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-06-23
- Publication Date
- 2025-03-07
AI Technical Summary
Orthodontic accessories in existing orthodontic therapies are usually visible on the tooth surface and have complex production processes that are difficult to meet aesthetics and customization needs.
A curable composition is developed that contains (meth)acrylate, urethane (meth)acrylate, photoinitiator, additive and surface treated nano-sized filler particles suitable for laminate manufacturing processes to produce highly transparent and aesthetic orthodontic accessories.
It has achieved the production of orthodontic accessories that are almost invisible on the surface of the teeth, with good physical and mechanical properties and wear comfort, simplified the production process and met the needs of aesthetics and customization.
Smart Images

Figure CN119584936A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a curable composition which can be processed in an additive-manufacturing process and which can be used to produce highly transparent orthodontic attachments for use in orthodontic appliance therapy. Background Art
[0002] In today's orthodontic appliance therapy, orthodontic attachments are used to support the movement of teeth.
[0003] Light-curable composite materials are currently used to make these orthodontic attachments.
[0004] Based on available shades and formulations, orthodontic attachments are often visible on the tooth surface and can detract from the overall aesthetics of orthodontic therapy.
[0005] Furthermore, since orthodontic attachments must fit the individual tooth surfaces of a patient, custom production of orthodontic attachments is required, which is often very troublesome.
[0006] WO 2021 / 130624 A1 (3M) describes articles, systems and techniques for manufacturing orthodontic attachments, for example, by an additive manufacturing process and positioning the attachments on a tooth surface using a transfer tray.
[0007] WO 2019 / 048963 A1 (3M) relates to a radiation curable composition comprising a radiation curable component, a photoinitiator and a filler material having a particle population in an amount greater than or equal to 50% by weight of the printable composition. The particle population exhibits a median diameter (D50) greater than or equal to 0.3 micrometers on a volume average basis.
[0008] WO 2019 / 104072 A1 (3M) describes an orthodontic article comprising a cured composition comprising the reaction product of: a free radical polymerizable resin comprising at least one monomer, oligomer and / or polymer comprising at least two (meth)acrylate moieties; a monofunctional reactive diluent; and a polymer comprising a free radical photoinitiator group.
[0009] US 9,795,541 B2 (Fontein et al.) relates to the use of a radically curable composition in a layered manufacturing process, preferably in stereolithography (SL) and digital light processing (DLP), the radically curable composition comprising linear and / or cyclic and / or cage-type polysiloxanes substituted by radically polymerizable groups and having at least 3 silicon atoms and / or mixed forms thereof; disiloxanes substituted by radically polymerizable groups; optionally one, two, three or more radically curable monomers without silicon atoms; fillers, initiators and / or catalysts for radical polymerization; and further conventional additives. Summary of the invention
[0010] Therefore, there is a need for a curable composition that can be processed using an additive manufacturing process and is suitable for producing customized orthodontic attachments for use in, for example, orthodontic appliance therapy.
[0011] It is desirable for the cured composition to have pleasing aesthetics in the patient's mouth.
[0012] Ideally, the cured composition should not be milky white and have adequate physical and mechanical properties.
[0013] Furthermore, the cured composition should also be sufficiently comfortable to wear and easy to clean, if possible.
[0014] One or more of these objectives may be achieved by the present invention as described in the text and claims.
[0015] In one embodiment, the invention features a curable composition as described in the claims and herein, comprising a (meth)acrylate free of urethane moieties, a urethane (meth)acrylate, a photoinitiator, an additive, discrete nanosized filler particles having an average particle size in the range of 10 nm to 40 nm and surface treated with a silane surface treatment agent selected from silane surface treatment agents comprising (meth)acrylate moieties, silane surface treatment agents not comprising (meth)acrylate moieties, and mixtures thereof, the discrete nanosized filler particles being present in an amount of 20 wt % or more, the curable composition not comprising the following components, alone or in combination, each in an amount of 2 wt % or more: aggregates of nanosized filler particles, agglomerates of nanosized filler particles, fumed silica, wt % relative to the entire composition.
[0016] Specifically, the curable compositions described herein do not contain a polymerizable component containing only one (meth)acrylate moiety in an amount of 1 wt % or more, wt % relative to the curable composition, and do not contain filler particles other than those described above in an amount of 2 wt % or more, respectively.
[0017] In another embodiment, the present invention relates to a cured composition obtainable by curing the curable composition as described in the claims and herein, preferably by processing the curable composition in a lamination manufacturing process.
[0018] Another embodiment of the present invention relates to a cured composition for use in a method for correcting teeth, the method comprising the steps of: attaching the cured composition described in the claims and this text to a tooth surface located in a patient's mouth by means of a tooth positioning tray; removing the tooth positioning tray; inserting a dental brace tray into the patient's mouth, the dental brace tray being engaged with the cured composition attached to the tooth surface, the cured composition having the shape of an orthodontic attachment, the orthodontic attachment having a transparency in the range of 60% to 85% measured on a 1 mm thick sample with light having a wavelength in the range of 400 nm to 700 nm, having a flexural strength of 50 MPa to 200 MPa measured according to ISO 4049 (2019), and comprising a (meth)acrylate free of urethane moieties, a urethane (meth)acrylate, and surface-treated discrete filler particles in an amount of 20 wt % to 50 wt %.
[0019] In another embodiment, the present invention is directed to a method of producing an orthodontic attachment comprising the step of processing the curable composition as described in the claims and herein by a lamination manufacturing process.
[0020] Yet another embodiment of the present invention is directed to a kit comprising a tooth positioning tray; and at least one curable composition as described in the claims and herein; or at least one cured composition as described in the claims and herein, and optionally a dental brace tray.
[0021] Unless defined differently, for the purpose of this specification, the following terms shall have the given meanings:
[0022] The term "compound" or "component" is a chemical substance having specific molecular properties or a chemical substance made from a mixture of such substances, such as a polymeric substance.
[0023] A "hardenable or curable or polymerizable component" is any component that can be cured or solidified by radiation-induced polymerization in the presence of a photoinitiator. The hardenable component may contain only one, two, three or more polymerizable groups. Typical examples of polymerizable groups include unsaturated carbon groups, such as vinyl groups, particularly present in (meth)acrylate groups.
[0024] As used herein, "(meth)acryloyl" is a shortened term that refers to "acryloyl" and / or "methacryloyl." For example, a "(meth)acryloyloxy" group is a shortened term that refers to an acryloyloxy group (i.e., CH2=CH-C(O)-O-) and / or a methacryloyloxy group (i.e., CH2=C(CH3)-C(O)-O-).
[0025] The "carbamate group" has a structure of "-NH-CO-O-".
[0026] As used herein, "hardening" or "curing" a composition are used interchangeably and refer to a polymerization and / or cross-linking reaction involving one or more materials contained in the composition, including, for example, photopolymerization and chemical polymerization techniques (e.g., ionic reactions or chemical reactions that form free radicals effective to polymerize ethylenically unsaturated compounds).
[0027] "Radiation curable" shall mean that the component (or composition, as the case may be) can be cured by applying radiation, preferably electromagnetic radiation having a wavelength in the spectral range of 350 nm to 500 nm, under ambient conditions and within a reasonable time frame (e.g. within about 15 min, 10 min or 5 min).
[0028] "Dental article" means an article used in the dental or orthodontic fields. Dental articles generally have two distinct surface parts, an outer surface and an inner surface. The outer surface is the surface that is generally not in permanent contact with the tooth surface. In contrast, the inner surface is the surface that is used to attach or fix the dental article to the tooth. If the dental article has the shape of a crown, the inner surface generally has a concave shape, while the outer surface generally has a convex shape. Dental articles should not contain components that are harmful to the patient's health and therefore do not contain hazardous and toxic components that can migrate out of the dental or orthodontic article.
[0029] "Orthodontic products" include orthodontic brackets, orthodontic accessories, buccal tubes, lingual retainers, orthodontic bands, bite openers, buttons and cleats, especially orthodontic brackets and orthodontic accessories.
[0030] "Particle" means a solid substance having a geometrically definable shape. The shape may be regular or irregular. Particles can generally be analyzed with respect to, for example, particle size and particle size distribution.
[0031] "Agglomeration" describes a weak association of particles that are usually held together by charge or polarity and that can break down into smaller entities. The specific surface area of the agglomerated particles does not differ substantially from that of the primary particles that make up the agglomerate (see DIN 53206; 1972).
[0032] Agglomerated fillers are available, for example, from Degussa, Cabot Corp. or Wacker under the product name Aerosil. ™ 、CAB-O-SIL ™ and HDK are commercially available.
[0033] "Non-agglomerated or discrete filler particles" means that the filler particles are present in the resin in discrete, non-associated (i.e., non-agglomerated and non-aggregated) stages. This can be demonstrated by TEM microscopy if desired.
[0034] Non-agglomerated nano-sized silica is available, for example, from Nalco Chemical Co. (Naperville, Ill.) under the product designation NALCO ™ COLLOIDAL SILICAS is commercially available, for example NALCO ™ Product numbers 1040, 1042, 1050, 1060, 2327 and 2329.
[0035] Non-agglomerated fillers are used and described, for example, in US 8,329,776 B2 (Hecht et al.) The content of this reference is incorporated herein by reference.
[0036] As used herein, "aggregated" describes a strong association of particles that are typically bound together by, for example, residual chemical treatment or partial sintering. The specific surface area of the aggregated particles is typically smaller than the specific surface area of the primary particles that make up the aggregate (see DIN 53206; 1972).
[0037] "Additive manufacturing" or "3D printing" refers to a process that involves creating an object layer by layer from digital data. The article can be of almost any shape or geometry and is produced from a three-dimensional model or other electronic data source.
[0038] There are many 3D printing technologies, one of which is vat polymerization that uses a radiation curing step to make three-dimensional articles. Examples of vat polymerization technologies include stereolithography (SLA) and digital light processing (DLP).
[0039] "Stereolithography" is an example of a layer-by-layer manufacturing technique, where a laser beam is aimed across the print area, typically using two motors, thereby solidifying the print resin. The process breaks down the design layer by layer into a series of dots.
[0040] "Digital light processing" is another example of an additive manufacturing technique, and typically involves using a digital projector screen to flash an image of each layer onto the build platform of the additive manufacturing unit. This image is typically made up of square pixels, resulting in a layer formed of small rectangular bricks called voxels.
[0041] An article is considered "opalescent" if the calculated opalescence value OP satisfies the following conditions:
[0042] ,
[0043] in
[0044] - is the red-green coordinate The difference between the transmission mode and the reflection mode in
[0045] - is the yellow-blue color coordinate The difference between the transmission mode and the reflection mode.
[0046] The degree of opalescence can be quantified by colorimetric spectrophotometric measurement with CIE standards (see US 6,232,367 (Kobashigawa et al.)).
[0047] "Environmental conditions" means the conditions to which the compositions described herein are typically subjected during storage and handling. Environmental conditions can be, for example, a pressure of 900 to 1,100 mbar, a temperature of 10°C to 40°C, and a relative humidity of 10% to 100%. In the laboratory, environmental conditions are typically adjusted to 20°C to 25°C and 1,000 to 1,025 mbar (at sea level).
[0048] As used herein, "a", "an", "the", "at least one", and "one or more" are used interchangeably. Also herein, numerical ranges recited by endpoints include all numbers subsumed within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0049] Adding "plural" to a term means that the term shall include both the singular and the plural. For example, the term "additive" refers to one additive and multiple additives (e.g., 2, 3, 4, etc.).
[0050] Unless otherwise indicated, all numbers expressing quantities of ingredients, measurements of physical properties (such as described below), and so forth, used in the specification and claims are to be understood as being modified in all instances by the term "about."
[0051] The terms "comprises" or "comprising" and variations thereof do not have a limiting meaning when these terms appear in the specification and claims. "Consisting essentially of means that certain additional components may be present, i.e., those components that do not materially affect the basic characteristics of the article or composition. "Consisting of means that no additional components should be present. The term "comprising" shall also include the terms "consisting essentially of" and "consisting of."
[0052] If a composition does not contain a certain component as an essential feature, then the composition is "substantially or substantially free of" the component. Thus, the component itself is not intentionally added to the composition, or the component is not intentionally added to the composition together with other components or ingredients of other components. A composition that is substantially free of a certain component generally does not contain the component at all. However, sometimes the presence of a small amount of the component is unavoidable, for example due to impurities contained in the raw materials used. "Substantially free" generally means an amount of less than 1%, 0.5% or 0.1% by weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 An orthodontic attachment according to the prior art is shown that is attached to a tooth surface for orthodontic appliance therapy.
[0054] Figure 2 3D printed orthodontic attachments based on printing resins containing nano-sized particles with different average particle sizes or without fillers are shown, which have different transparencies, respectively, with different opalescence values.
[0055] Figure 3 An orthodontic attachment produced with the curable composition described herein and attached to a tooth surface is shown. DETAILED DESCRIPTION
[0056] The compositions and methods described herein have been found to have several advantageous properties.
[0057] The curable composition can be processed in an additive manufacturing process, ie the curable composition is 3D printable.
[0058] Furthermore, since the filler particles are in discrete stages, they are curable and the cured composition is highly transparent.
[0059] The cured composition is also generally not milky, which can further improve clarity.
[0060] This is advantageous because the composition can be more easily processed and cured in additive manufacturing processes and also enables 3D printing of small and delicate structures such as orthodontic products.
[0061] Thus, the composition can be used to manufacture orthodontic articles which can subsequently be attached to tooth surfaces.
[0062] If desired, the orthodontic article may be inserted into the positioning tray and applied to the tooth surface.
[0063] Furthermore, due to its transparency or translucency and the absence of opalescence, the cured composition is highly aesthetic and orthodontic articles made therefrom are barely visible on the tooth surface.
[0064] Furthermore, the article obtained or obtainable after curing of the curable composition has advantageous mechanical properties, in particular with regard to flexural strength, E-modulus and / or deformation.
[0065] It has also been found that the curable composition is capable of producing a cured composition or article having a smooth surface. If the article has the shape of an orthodontic attachment for use in a patient's mouth, this can provide a "soft feel" effect and increase wearing comfort.
[0066] The smooth surface is also easy to clean, thus helping to prevent staining and discoloration of the dental attachment over time.
[0067] The curable compositions described herein can be characterized as one-component photocurable compositions.
[0068] The curable composition can be further characterized by the following characteristics, alone or in combination: Viscosity: at 23°C, shear rate 1s -1 hour, ; or at 23°C, shear rate of 1s -1 At 1 To less than 50 range; capable of being cured by radiation having a wavelength in the range of 350nm to 500nm or 350nm to 420nm.
[0069] The viscosity of the curable composition within the above range is found to be particularly suitable for processing the curable composition in a lay-up manufacturing process.
[0070] Due to the high transparency, there is less light scattering, which makes it easier to produce highly detailed articles.
[0071] The curable composition comprises one or more (meth)acrylate components that do not comprise a urethane moiety.
[0072] (Meth)acrylates that do not include a urethane moiety differ from urethane (meth)acrylates, for example, in functionality, chemical moiety, molecular weight, or a combination thereof.
[0073] The (meth)acrylate component that does not contain urethane moieties can generally be characterized by the following properties alone or in combination: contains at least 2 (meth)acrylate moieties; molecular weight (Mw): 170 g / mol to 1,000 g / mol.
[0074] Examples include diacrylates or polyacrylates and methacrylates such as glycerol diacrylate, glycerol triacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, 1,3-propylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,2,4-butanetriol trimethacrylate, 1,4-cyclohexanediol diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, sorbitol hexaacrylate, bis[1-(2-acryloyloxy)]-p-ethoxyphenyldimethylmethane, bis[1-(3-acryloyloxy-2-hydroxy)]-p-propoxyphenyl-dimethylmethane; diacrylates and dimethacrylates of polyethylene glycol having a molecular weight of 200 g / mol to 500 g / mol, acrylated monomers such as US 4,652,274) and acrylated oligomers (such as those of US 4,642,126); and vinyl compounds such as diallyl phthalate, divinyl succinate, divinyl adipate, and divinyl phthalate.
[0075] Preferred ethylenically unsaturated monomers are methacrylates and acrylate monomers, such as di(meth)acrylates of propylene glycol, butanediol, hexanediol, octanediol, nonanediol, decanediol and eicosanediol, di(meth)acrylates of ethylene glycol, polyethylene glycol and polypropylene glycol, di(meth)acrylates of ethoxylated bisphenol A, for example 2,2'-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane and (meth)acrylamide. The monomers used may also be esters of [α]-cyanoacrylic acid, crotonic acid, cinnamic acid and sorbic acid.
[0076] It is also possible to use methacrylates such as those mentioned in US Pat. No. 4,795,823 (Schmitt et al.), including triglycolic acid bis[3[4]-methacryloyloxymethyl-8(9)-tricyclo[5.2.1.0 2,6Particularly suitable are 2,2-bis-4 (3-methacryloyloxy-2-hydroxypropoxy) phenylpropane (Bis-GMA), 2,2-bis-4 (3-methacryloyloxypropoxy) phenylpropane, triethylene glycol dimethacrylate (TEGDMA) and bishydroxymethyl tricyclo-(5.2.1.0 2,6 )decane di(meth)acrylate.
[0077] The (meth)acrylate component that does not contain a urethane moiety is typically present in an amount of at least 20 wt%, or at least 25 wt%, or at least 30 wt%; or up to 75 wt%, or up to 70 wt%, or up to 65 wt%; or from 20 wt% to 75 wt%, or from 25 wt% to 70 wt%, or from 30 wt% to 65 wt%; wt% relative to the total composition.
[0078] The curable composition comprises one or more urethane (meth)acrylates. The urethane (meth)acrylates typically comprise at least two (meth)acrylate moieties and at least two urethane moieties.
[0079] The molecular weight (Mw) of the urethane (meth)acrylate is at least 400 g / mol, or at least 800 g / mol, or at least 1,000 g / mol. Useful ranges include from 400 g / mol to 3,000 g / mol, or from 800 g / mol to 2,700 g / mol, or from 1,000 g / mol to 2,500 g / mol.
[0080] The urethane (meth)acrylate employed in the composition is typically obtained by reacting an NCO terminated compound with a suitable monofunctional (meth)acrylate monomer such as hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, preferably hydroxyethyl methacrylate and hydroxypropyl methacrylate.
[0081] Urethane (meth)acrylates can be obtained by various methods known to those skilled in the art.
[0082] For example, polyisocyanates and polyols can be reacted to form isocyanate-terminated urethane prepolymers, which are then reacted with (meth)acrylates such as 2-hydroxyethyl (meth)acrylate. These types of reactions can be carried out at room temperature or higher, optionally in the presence of catalysts such as tin catalysts, tertiary amines, etc.
[0083] The polyisocyanate useful in forming the isocyanate functional urethane prepolymer may be any organic isocyanate having at least two free isocyanate groups, including aliphatic, cycloaliphatic, aromatic and araliphatic isocyanates.
[0084] Any known polyisocyanate may be employed, such as alkyl and alkylene polyisocyanates, cycloalkyl and cycloalkylene polyisocyanates, and combinations such as alkylene and cycloalkylene polyisocyanates.
[0085] Preferably, diisocyanates of the formula X(NCO)2 are used, in which X represents an aliphatic hydrocarbon radical having 2 to 12 C atoms, a cycloaliphatic hydrocarbon radical having 5 to 18 C atoms, an aromatic hydrocarbon radical having 6 to 16 C atoms and / or an araliphatic hydrocarbon radical having 7 to 15 C atoms.
[0086] Examples of suitable polyisocyanates include 2,2,4-trimethylhexamethylene-1,6-diisocyanate, hexamethylene-1,6-diisocyanate (HDI), cyclohexyl-1,4-diisocyanate, 4,4'-methylene-bis(cyclohexyl isocyanate), 1,1'-methylenebis(4-isocyanato)cyclohexane, isophorone diisocyanate, 4,4'-methylene diphenyl diisocyanate, 1,4-tetramethylene diisocyanate, m-tetramethylxylene diisocyanate and p-tetramethylxylene diisocyanate, 1,4-phenylene diisocyanate, 2,6-toluene diisocyanate and 2,4-toluene diisocyanate, 1,5-naphthylene diisocyanate, 2,4'-diphenylmethane diisocyanate and 4,4'-diphenylmethane diisocyanate, and mixtures thereof.
[0087] It is also possible to use the higher-functional polyisocyanates or modified polyisocyanates known in polyurethane chemistry, for example modified polyisocyanates containing carbodiimide groups, allophanate groups, isocyanurate groups and / or biuret groups. Particularly preferred isocyanates are isophorone diisocyanate, 2,4,4-trimethyl-hexamethylene diisocyanate and higher-functional polyisocyanates with isocyanurate structures.
[0088] The isocyanate terminated urethane compound is terminated with a (meth)acrylate to produce a urethane (meth)acrylate compound. Generally speaking, any (meth)acrylate type capping agent having a terminal hydroxyl group and also having an acrylic or methacrylic moiety can be employed, with methacrylic moieties being preferred.
[0089] Examples of suitable end-capping agents include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, glycerol di(meth)acrylate and / or trimethylolpropane di(meth)acrylate. Particularly preferred is 2-hydroxyethyl methacrylate (HEMA) and / or 2-hydroxyethyl acrylate (HEA).
[0090] The equivalent ratio of isocyanate groups to the compound reactive with respect to isocyanate groups is from 1.1:1 to 8:1, preferably from 1.5:1 to 4:1.
[0091] The isocyanate polyaddition reaction can be carried out in the presence of catalysts known in polyurethane chemistry, for example organotin compounds such as dibutyltin dilaurate, or amine catalysts such as diazabicyclo[2.2.2]octane. In addition, the synthesis can be carried out in the melt or in a suitable solvent, which can be added before or during the preparation of the prepolymer. Suitable solvents are, for example, acetone, 2-butanone, tetrahydrofuran, dioxane, dimethylformamide, N-methyl-2-pyrrolidone (NMP), ethyl acetate, alkyl ethers of ethylene glycol and propylene glycol, and aromatic hydrocarbons. Particular preference is given to using ethyl acetate as solvent.
[0092] Suitable examples of urethane (meth)acrylates include 7,7,9-trimethyl-4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-dioxy-dimethacrylate (e.g., Plex 666-1, Röhm), urethane (meth)acrylates derived from 1,4-bis(1-isocyanato-1-methylethyl)benzene and 1,3-bis(1-isocyanato-1-methylethyl)benzene (e.g., as described in EP 0 934 926 A1), and mixtures thereof.
[0093] According to one embodiment, the urethane (meth)acrylate is characterized as follows:
[0094] With structure A-(-S1-U-S2-MA) n ,in
[0095] A is a connector element comprising at least one unit,
[0096] S1 is a spacer group comprising at least 4 units connected to each other,
[0097] S2 is a spacer group comprising at least 4 units connected to each other,
[0098] Units A, S1 and S2 are independently selected from CH3-, -CH2-, -O-, -S-, -NR 1 -、-CO-、-CR 1 =、 , , , , 、-N=、-CR 1 R 2 -,
[0099] wherein R1 and R2 are independently selected from hydrogen, alkyl, substituted alkyl, alkenyl, cycloalkyl, substituted cycloalkyl, arylalkyl, aryl or substituted aryl, wherein these units may form linear, branched or cyclic structures such as alkyl, cycloalkyl, aryl, ester, carbamate or amide groups,
[0100] U is a carbamate group connecting the spacer groups S1 and S2,
[0101] MA is an acrylate or methacrylate group, and
[0102] n is 3 to 6.
[0103] According to one embodiment, the urethane (meth)acrylate is represented by the following structure:
[0104] A(-S1-U-S2-MA) n
[0105] in
[0106] A is a connector element comprising at least 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 units,
[0107] S1 is a spacer group comprising units linked to each other and comprising at least 4, 5, 6, 7, 8, 9 or 10 units,
[0108] S2 is a spacer group comprising units linked to each other and comprising at least 4, 5, 6, 7, 8, 9, 10, 12, 15, 20 or 25 units,
[0109] U is a carbamate group connecting the spacer groups S1 and S2,
[0110] MA is an acrylate or methacrylate group, and
[0111] n is 3-6, or 4-6, or 5-6.
[0112] It may be preferred if A has a cyclic structure and comprises at least about 6 units.
[0113] It may further be preferred if S1 has a linear or branched structure and comprises at least 4 or 6 units.
[0114] It may further be preferred if S2 has a linear or branched structure and comprises at least 6 or 8 units.
[0115] Also preferred are urethane (meth)acrylates in which A has a cyclic structure and contains at least 6 units, and S1 has a linear structure and contains at least 4 units, and S2 has a linear structure and contains at least 8 units, and U is a urethane group.
[0116] The atoms of the urethane groups and the atoms of the (meth)acryloyl groups connecting S1 and S2 do not belong to the spacer group S1 or S2. Therefore, the atoms of the urethane groups are not counted as units of the spacer group S1 or S2.
[0117] The nature and structure of the connector element are not particularly limited. The connector element may contain saturated (no double bonds) or unsaturated (at least one or two double bonds) units, aromatic or heteroaromatic units (containing aromatic structures including N, O and S atoms).
[0118] Specific examples of the connector element A having a ring structure include:
[0119] (6 units) (6 units)
[0120] Specific examples of connector elements A having a non-cyclic but branched structure include:
[0121] (5 units) (1 unit)
[0122] (16 units) (15 units)
[0123] (12 units) (15 units)
[0124] (17 units)
[0125] (10 units) (13 units) (16 units)
[0126] The dashed line represents the bond to the spacer group S1.
[0127] The nature and structure of the spacer group S1 or S2 are also not particularly limited.
[0128] The spacer group contains units connected to each other. Typical units include: CH3-, -CH2-, -O-, -S-, -NR 1 -、-CO-、-CR 1 =、 , , , , 、-N=、-CR 1 R 2 -, where R 1 and R 2 are independently selected from hydrogen, alkyl, substituted alkyl, alkenyl, cycloalkyl, substituted cycloalkyl, arylalkyl, aryl or substituted aryl.
[0129] These units may form linear, branched or cyclic structures such as alkyl, cycloalkyl, aryl, ester, carbamate or amide groups.
[0130] The structure of S1 may be the same as the structure of S2. However, in some embodiments, the structure of S1 is different from S2. In a specific embodiment, the number of units present in S1 is less than or equal to the number of units present in S2.
[0131] In a specific embodiment, S1 may have a saturated hydrocarbon structure.
[0132] In another specific embodiment, S2 may have a saturated hydrocarbon structure.
[0133] Typical examples of spacer groups that can be used for S1 include:
[0134] (4 units) (6 units) (8 units)
[0135] (13 units) (13 units) (8 units) (8 units)
[0136] The dashed lines represent chemical bonds to the group A or the group U.
[0137] Typical examples of spacer groups that can be used for S2 include:
[0138] (9 units)
[0139] (16 units)
[0140] (6 units)
[0141] The dashed line represents the chemical bonding to the (meth)acrylate group or to the group U. The number of units counted according to the invention is given in brackets.
[0142] Specific examples of urethane (meth)acrylates include:
[0143]
[0144]
[0145]
[0146] Further suitable urethane (meth)acrylates are based on α-ω-terminated poly(meth)acrylate diols (eg as described in EP 1 242 493 B1), or may be polyesters, polyethers, polybutadienes or polycarbonate urethane (meth)acrylates (eg as described in US Pat. No. 6,936,642 B2).
[0147] The urethane (meth)acrylate is typically present in an amount of at least 5 wt%, or at least 8 wt%, or at least 10 wt%; or up to 25 wt%, or up to 20 wt%, or up to 15 wt%; or from 5 wt% to 25 wt%, or from 8 wt% to 20 wt%, or from 10 wt% to 15 wt%; wt% relative to the total composition.
[0148] The (meth)acrylate not comprising a urethane moiety is generally used in an amount in excess by weight over the (meth)acrylate comprising a urethane moiety.
[0149] The ratio of ((meth)acrylate not containing a urethane moiety) / ((meth)acrylate containing a urethane moiety) is generally in the range of 10 / 1 to 2 / 1 with respect to weight.
[0150] The curable composition comprises a photoinitiator. If desired, one or more photoinitiators may be used.
[0151] In order to process the curable composition in a lamination manufacturing process, the photoinitiator should have a light absorption peak in the range of 350 nm to 500 nm.
[0152] Suitable photoinitiators include acylphosphine oxides.
[0153] Acylphosphine oxides can be characterized by the following formula:
[0154] (R 9 )2-P(=O)-C(=O)-R 10
[0155] Each R 9 R is independently a hydrocarbon group such as alkyl, cycloalkyl, aryl and aralkyl, any of which may be substituted by a halogen, alkyl or alkoxy group, or both R 9The groups may be joined to form a ring together with the phosphorus atom, and wherein R 10 is a hydrocarbon group, a five- or six-membered heterocyclic group containing S-, O- or N-, or -ZC(=O)-P(=O)-(R 9 )2 group, wherein Z represents a divalent hydrocarbon group such as an alkylene group or a phenylene group having 2 to 6 carbon atoms.
[0156] Suitable systems are also described, for example, in US 4,737,593 (Ellrich et al.), the contents of which are incorporated herein by reference.
[0157] Preferred acylphosphine oxides are those in which R 9 and R 10 The groups are those of phenyl or phenyl substituted with lower alkyl or lower alkoxy. By "lower alkyl" and "lower alkoxy" are meant such groups having 1 to 4 carbon atoms. In particular, 2,4,6-trimethylbenzoyldiphenylphosphine oxide has been found to be useful (Lucirin ™ TPO, BASF).
[0158] More specific examples include bis-(2,6-dichlorobenzoyl)phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-ethoxyphenyl-phosphine oxide, bis-(2,6-dichlorobenzoyl)-4-biphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2-naphthylphosphine oxide, bis-(2,6-dichlorobenzoyl)-1-naphthylphosphine oxide , bis-(2,6-dichlorobenzoyl)-4-chloro-phenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,4-dimethoxyphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)decylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-octylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dimethoxybenzoyl)-phenylphosphine oxide, bis-(2,4,6-trimethylbenzoyl)-2,5-dimethylphenylphosphine oxide phosphine oxide, bis-(2,6-dichloro-3,4,5-trimethoxybenzoyl)-2,5-dimethylphenylphosphine oxide, bis-(2,6-dichloro-3,4,5-trimethoxybenzoyl)-4-ethoxyphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-2,5-dimethyl-phenylphosphine oxide, bis-(2-methyl-1-naphthoyl)phenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-4-biphenylphosphine oxide, bis-(2-methyl-1-naphthoyl)-4-ethoxyphenylphosphine oxide phosphine, bis-(2-methyl-1-naphthoyl)-2-naphthyl phosphine oxide, bis-(2-methyl-1-naphthoyl)-4-propylphenyl phosphine oxide, bis-(2-methyl-1-naphthoyl)-2,5-dimethyl phosphine oxide, bis-(2-methoxy-1-naphthoyl)-4-ethoxyphenyl phosphine oxide, bis-(2-methoxy-1-naphthoyl)-4-biphenyl phosphine oxide, bis-(2-methoxy-1-naphthoyl)-2-naphthyl phosphine oxide and bis-(2-chloro-1-naphthoyl)-2,5-dimethylphenyl phosphine oxide.
[0159] The acylphosphine oxide bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (formerly known as IRGACURE from Ciba Specialty Chemicals) is sometimes preferred. ™ 819).
[0160] Suitable photoinitiators also include binary and ternary photoinitiator systems. Typical ternary photoinitiators include iodonium salts, photosensitizers, and electron donor compounds, as described in US 5,545,676 (Palazzotto et al.). Suitable iodonium salts include diaryl iodonium salts, such as diphenyl iodonium chloride, diphenyl iodonium hexafluorophosphate, and diphenyl iodonium tetrafluoroborate. Suitable photosensitizers are monoketones and diketones. Particularly suitable photosensitizers include alpha diketones. Examples include camphorquinone, benzil, 3,3,6,6-tetramethyl-cyclohexanedione, phenylanthraquinone, 1-phenyl-1,2-propanedione, and other 1-aryl-2-alkyl-1,2-ethanediones and cyclic alpha diketones. Suitable electron donor compounds include substituted amines. In particular, tertiary amines are generally used.
[0161] In addition to the photoinitiator, a reducing agent may also be present. The combination of photoinitiator and reducing agent is often referred to as a photoinitiator system. As reducing agent or donor component, tertiary amines are often used.
[0162] Suitable examples of tertiary amines include N,N-dimethyl-p-toluidine, N,N-dimethyl-aminoethyl methacrylate, triethanolamine, 4-dimethylaminobenzoic acid methyl ester, 4-dimethyl-aminobenzoic acid ethyl ester, methyldiphenylamine, and 4-dimethylaminobenzoic acid isopentyl ester.
[0163] The photoinitiator is typically present in an amount of at least 0.01 wt%, or at least 0.02 wt% or at least 0.03 wt%; or up to 5 wt%, or up to 4 wt% or up to 3 wt%; or from 0.01 wt% to 5 wt%, or from 0.02 wt% to 4 wt% or from 0.03 wt% to 3 wt%; wt% relative to the weight of the composition.
[0164] The curable composition comprises discrete nano-sized filler particles.
[0165] The average particle size of the discrete nano-sized filler particles is 40 nm and below, or 35 nm and below, or 30 nm and below. The average particle size is typically in the range of 10 nm to 40 nm, or 10 nm to 35 nm, or 10 nm to 30 nm.
[0166] The discrete nano-sized filler particles generally comprise oxides of Si, Zr, Al, and mixtures thereof, with oxides of Si and Zr sometimes being preferred.
[0167] The specific surface area (BET) of the nano-sized filler particles is preferably 80 m 2 / g or more, or 100m 2 / g or more, or 120m 2 / g or more. The specific surface area (BET) is usually 80m 2 / g to 500m2 / g, or 100m 2 / g to 400m 2 / g or 120m 2 / g to 300m 2 If necessary, the Brunauer, Emmet and Teller (BET) method can be used by using a device purchased from Quantachrome (Monosorb ™ ) to determine the specific surface area.
[0168] Preferred nano-sized silica is available from Nalco Chemical Company of Napaville, Illinois, USA under the product designation NALCO ™ COLLOIDAL SILICAS is commercially available. For example, preferred silica particles can be obtained by using NALCO ™ Products 1040, 1042, 1050, 1060, 2327 and 2329 are available. Other suitable nano-sized silicas are available from Covestro (Leverkusen, Germany) under the product designation Dispercoll ™ (e.g. Dispercoll ™ S 3030 or Dispercoll ™ S 4020), Grace GmbH & Co. KG (Worms, Germany) uses the Ludox ™ (e.g. Ludox ™ P-X30 or Ludox ™ P-W30) and Nouryon (Amsterdam, Netherlands) with the product label Levasil ™ (e.g. Levasil ™ CS50-34P) was purchased commercially.
[0169] The discrete nano-sized filler particles are surface treated. A useful surface treatment agent is silane.
[0170] The silane surface treatment agent may or may not contain a polymerizable moiety, particularly a (meth)acrylate moiety. Only one silane surface treatment agent or a mixture of different silane treatment agents may be used.
[0171] In one specific embodiment, a mixture of silane surface treatment agents comprising a polymerizable moiety, particularly a (meth)acrylate moiety, and silane surface treatment agents that do not comprise a polymerizable moiety are used.
[0172] Surface treatment makes nano-sized filler particles more easily dispersed in the monomer matrix and can prevent the filler from settling out of the formulation during storage.
[0173] If two different silane surface treatment agents are used for the surface treatment, the polymerizable silane surface treatment agent is used in a higher amount by weight than the non-polymerizable silane surface treatment agent.
[0174] Ratios of polymerizable silane surface treatment agent to non-polymerizable silane surface treatment agent by weight ranging from 90 / 10 to 60 / 40 or from 80 / 20 to 70 / 30 have been found to be useful.
[0175] If desired, the surface of the treated particles can be analyzed using FT-IR or NMR techniques.
[0176] The polymerizable silane surface treatment agent is typically an alkoxysilane, preferably a trialkoxysilane containing a (meth)acrylate group.
[0177] A typical embodiment can be characterized by the following formula:
[0178] A m BSi(R 1 ) n (OR 2 ) 3-n
[0179] wherein A comprises a (meth)acryloyl moiety,
[0180] B includes a spacer group, such as (i) a linear or branched C1 to C 12 Alkyl, (ii) C6 to C 12 aryl, (iii) an organic radical having 2 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds,
[0181] R 1 including alkyl groups (e.g. C1 to C6) or aryl groups (e.g. C6 to C 12 ),and
[0182] R 2 including alkyl groups (e.g. C1 to C6),
[0183] Where m=1, 2 or 3, and n=0, 1 or 2.
[0184] Examples of (meth)acrylate functionalized trialkoxysilanes include, but are not limited to, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltri(methoxyethoxy)silane, 3-(meth)acryloxyacryltrimethoxysilane, (meth)acryloxyethyldimethyl(3-trimethoxysilylpropyl)ammonium chloride, N-(3-(meth)acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, O-((meth)acryloxyethyl)-N-(triethoxysilylpropyl)-carbamate, (meth)acryloxy-methyltrimethoxysilane, (meth)acryloxymethyltriethoxysilane, (meth)acryloxymethylmethyldimethoxysilane, (meth)acryloxymethyl [(meth)acryloxymethyl]phenethyltrimethoxysilane, O-[(meth)acryloxyethyl]-N-(triethoxysilylpropyl)carbamate, (meth)acryloxypropyltriisopropoxy-silane, (meth)acryloxypropylmethyldimethoxysilane, (meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylmethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, (meth)acryloxymethyldimethylmethoxysilane, (meth)acryloxymethyldimethylethoxysilane, oligomeric hydrolysis products of 3-(meth)acryloxypropyltrimethoxysilane, and oligomeric hydrolysis products of 3-(meth)acryloxypropyltriethoxysilane.
[0185] The non-polymerizable silane surface treatment agent is typically an alkoxysilane, preferably a trialkoxysilane.
[0186] A typical embodiment can be characterized by the following formula:
[0187] DSi(R 1 ) n (OR 2 ) 3-n
[0188] wherein D comprises (i) a linear or branched unsubstituted or substituted (e.g., substituted with one or more amino or thiol groups) C1 to C 16 (ii) unsubstituted or substituted (e.g., substituted with one or more amino or mercapto groups) C6 to C 12 an aryl group, or (iii) an organic group having 2 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds,
[0189] R1 including alkyl groups (e.g. C1 to C6) or aryl groups (e.g. C6 to C 12 ),and
[0190] R 2 including alkyl groups (e.g. C1 to C6),
[0191] Where n=0, 1 or 2.
[0192] Suitable non-polymerizable silane surface treatment agents include phenyltrimethoxysilane, phenyltriethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, hexadecyltrimethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, propyltrimethoxysilane, 3-aminopropyl-methyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-cyclohexyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, (cyclohexyl)methyldimethoxysilane, and mixtures thereof.
[0193] Polymerizable and non-polymerizable silane surface treatment agents are available, for example, from Wacker (München, Germany) under the product designation Geniosil ™ or from Evonik (Hanau, Germany) with the product label Dynasylan ™ Commercially available.
[0194] The method for surface treating discrete nano-sized filler particles generally comprises the following steps:
[0195] mixing a sol containing nano-sized particles with a silane surface treatment agent and stirring the mixture under reflux in a solvent such as ethanol for several hours (e.g., 2 hours to 10 hours);
[0196] After stirring for several hours (e.g., 2 hours to 10 hours), undermixing the monomer into the resulting mixture, and stirring again for several hours (e.g., 2 hours to 10 hours);
[0197] The solvent was removed in vacuo.
[0198] Suitable methods are also described in US 6,899,948 (Zhang et al.).
[0199] The curable composition does not include filler particles other than those described herein in an amount of 2 wt % or more, respectively.
[0200] Specifically, the following filler components are not present, either alone or in combination: aggregates of nano-sized filler particles; agglomerates of nano-sized filler particles; fumed silica, wherein the average particle size of the primary filler particles is in the range of 10 nm to 40 nm.
[0201] Thus, the curable composition is substantially free of fillers comprising nano-sized filler particle clusters, fumed silica, and mixtures thereof.
[0202] It has been found that the presence of these filler components may have undesirable effects on rheology, clarity and / or opacity.
[0203] The discrete nano-sized filler particles are typically present in an amount of at least 20 wt%, or at least 25 wt%, or at least 30 wt%; or up to 50 wt%, or up to 45 wt%, or up to 40 wt%; or from 20 wt% to 50 wt%, or from 25 wt% to 45 wt%, or from 30 wt% to 40 wt%; wt% relative to the total composition.
[0204] Use of such amounts of fillers generally contributes to the physical and mechanical properties of the composition, particularly in its cured state.
[0205] The curable composition typically also includes one or more additives.
[0206] Additives that may be present include stabilizers, fluorescent dyes, UV light absorbers, and mixtures thereof.
[0207] Suitable stabilizers include free radical scavengers such as substituted and / or unsubstituted hydroxyaromatic compounds (e.g., butylated hydroxytoluene (BHT), hydroquinone, hydroquinone monomethyl ether (MEHQ), 3,5-di-tert-butyl-4-hydroxyanisole (2,6-di-tert-butyl-4-ethoxyphenol), 2,6-di-tert-butyl-4-(dimethylamino)methylphenol or 2,5-di-tert-butylhydroquinone, 2-(2'-hydroxy-5'-methylphenyl)- 2H-benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)-2H-benzotriazole, 2-hydroxy-4-methoxybenzophenone (UV-9), 2-(2'-hydroxy-4',6'-di-tert-amylphenyl)-2H-benzotriazole, 2-hydroxy-4-n-octyloxybenzophenone, 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, phenothiazine and hindered amine light stabilizers (HALS).
[0208] Suitable fluorescent dyes typically include anthracene or perylene moieties.
[0209] Fluorescent dyes generally have an absorption peak in the range of 350 nm to 450 nm.
[0210] Commercially available fluorescent dyes include, for example, Lumilux ™ Blau LZ, Lumilux ™ Gelb LZ and dyes containing an anthracene moiety (e.g., 2-ethyl-9,10-dimethoxyanthracene; EDMO).
[0211] If present, the fluorescent dye is generally present in an amount of 0.001% to 0.5% by weight relative to the weight of the composition.
[0212] Suitable UV light absorbers include components containing benzotriazole moieties.
[0213] UV absorbers generally have an absorption peak in the range of 350 nm to 420 nm.
[0214] Commercially available UV light absorbers include Tinuvin ™ 326. Tinuvin ™ 328. Tinuvin ™ P. Uvinul ™ M40.
[0215] If present, UV light absorbers are generally present in amounts of 0.001% to 1.0% by weight relative to the weight of the composition.
[0216] The additive is typically present in an amount of at least 0.001 wt%, or at least 0.01 wt% or at least 0.1 wt%; or up to 10 wt%, or 7.5 wt% or 5 wt%; or from 0.001 wt% to 10 wt%, or from 0.01 wt% to 7.5 wt% or from 0.1 wt% to 5 wt%; wt% relative to the total composition.
[0217] The curable compositions described herein generally do not contain the following components, alone or in combination: an amount of 1 wt % or more of a polymerizable component containing an acidic moiety; an amount of 1 wt % or more of a polymerizable component containing only one (meth)acrylate moiety; an amount of 1 wt % or more of a plasticizer; the wt % is relative to the weight of the curable composition. Thus, the curable composition is substantially free of these components.
[0218] For example, the presence of a polymerizable component comprising only one (meth)acrylate moiety in an amount of 1 wt% or more may have an undesirable effect on mechanical properties such as E-modulus. Compositions comprising a polymerizable component comprising only one (meth)acrylate moiety in an amount of 1 wt% or more are sometimes considered to be too flexible.
[0219] The curable compositions described herein generally comprise, consist essentially of, or consist of the following amounts of the respective components:
[0220] Methacrylates not containing urethane moieties: 20 to 75 wt %,
[0221] Urethane (meth)acrylate: 5% to 25% by weight,
[0222] Photoinitiator: 0.01 wt% to 5 wt%,
[0223] Discrete surface treated nano-sized filler particles: 20% to 50% by weight,
[0224] Additives: 0.001 wt % to 10 wt %, wt % relative to the entire composition.
[0225] The curable composition may also comprise, consist essentially of, or consist of the following amounts of the respective components:
[0226] Methacrylates not containing urethane moieties: 25 to 70 wt %,
[0227] Urethane (meth)acrylate: 8% to 20% by weight,
[0228] Photoinitiator: 0.02 wt% to 4 wt%,
[0229] Discrete surface treated nano-sized filler particles: 25 wt% to 45 wt%,
[0230] Additives: 0.01 wt% to 7.5 wt%, wt% relative to the entire composition.
[0231] The curable composition may also comprise, consist essentially of, or consist of the following amounts of the respective components:
[0232] Methacrylates not containing urethane moieties: 30 to 65 wt %,
[0233] Urethane (meth)acrylate: 10% to 15% by weight,
[0234] Photoinitiator: 0.03 wt% to 3 wt%,
[0235] Discrete surface treated nano-sized filler particles: 30% to 40% by weight,
[0236] Additives: 0.1 wt% to 5 wt%, wt% relative to the entire composition.
[0237] More specific embodiments of the curable composition are given below:
[0238] Implementation 1
[0239] A curable composition comprising, consisting essentially of, or consisting of:
[0240] a. (meth) acrylate not comprising a urethane moiety in an amount of 20 wt % to 75 wt %,
[0241] b. urethane (meth) acrylate in an amount of 5% to 25% by weight,
[0242] c. Photoinitiator,
[0243] d. Discrete nano-sized filler particles, the discrete nano-sized filler particles
[0244] having an average particle size in the range of 10 nm to 40 nm,
[0245] The surface has been treated with a silane surface treatment agent selected from
[0246] Silane surface treatment agents comprising a (meth)acrylate moiety,
[0247] A silane surface treatment agent that does not contain a (meth)acrylate moiety, and
[0248] A mixture of these, and
[0249] The discrete nano-sized filler particles are present in an amount of 20% to 50% by weight,
[0250] e. Additives,
[0251] The curable composition does not comprise the following components, either alone or in combination:
[0252] Aggregates of nano-sized filler particles,
[0253] Agglomerates of nano-sized filler particles,
[0254] Fumed silica,
[0255] The amount of each is 2% by weight or more, the % by weight being relative to the entire composition.
[0256] Implementation 2
[0257] A curable composition comprising, consisting essentially of, or consisting of:
[0258] a. (meth) acrylate not comprising a urethane moiety in an amount of 20 wt % to 75 wt %,
[0259] b. urethane (meth) acrylate in an amount of 8 wt % to 20 wt %,
[0260] c. Photoinitiator,
[0261] d. Discrete nano-sized filler particles, the discrete nano-sized filler particles
[0262] having an average particle size in the range of 10 nm to 40 nm,
[0263] The surface has been treated with a silane surface treatment agent selected from
[0264] Silane surface treatment agents comprising a (meth)acrylate moiety,
[0265] A silane surface treatment agent that does not contain a (meth)acrylate moiety, and
[0266] A mixture of these, and
[0267] The discrete nano-sized filler particles are present in an amount of 25% to 45% by weight,
[0268] e. Additives,
[0269] The curable composition does not comprise the following components, either alone or in combination:
[0270] Aggregates of nano-sized filler particles,
[0271] Agglomerates of nano-sized filler particles,
[0272] Fumed silica,
[0273] The amount of each is 2% by weight or more, the % by weight being relative to the entire composition.
[0274] Implementation 3
[0275] A curable composition comprising, consisting essentially of, or consisting of:
[0276] a. (meth) acrylate not comprising a urethane moiety in an amount of 20 wt % to 75 wt %,
[0277] b. urethane (meth) acrylate in an amount of 8 wt % to 20 wt %,
[0278] c. Photoinitiator,
[0279] d. Discrete nano-sized filler particles, the discrete nano-sized filler particles
[0280] having an average particle size in the range of 10 nm to 40 nm, and
[0281] has been surface treated with a surface treatment agent comprising a (meth)acrylate moiety and a surface treatment agent not comprising a (meth)acrylate moiety, wherein preferably, the surface treatment agent comprising a (meth)acrylate moiety is used in a higher amount by weight than the surface treatment agent not comprising a (meth)acrylate moiety,
[0282] The discrete nano-sized filler particles are present in an amount of 25% to 45% by weight,
[0283] e. Additives,
[0284] The curable composition does not comprise the following components, either alone or in combination:
[0285] Aggregates of nano-sized filler particles,
[0286] Agglomerates of nano-sized filler particles,
[0287] Fumed silica,
[0288] The amount of each is 2% by weight or more, the % by weight being relative to the entire composition.
[0289] The curable composition described herein can be produced by mixing the corresponding components under light-protected conditions. If necessary, a high-speed mixer can be used.
[0290] During storage, the curable compositions described in this text are usually stored under light-protected conditions, in particular in sealed containers, vessels or foil bags. The volume of the container may range from 1 ml to 1 1.
[0291] The curable composition can be processed in a laminate manufacturing process to produce a 3d printed article. 3d printing methods are generally known to those skilled in the art.
[0292] An example of this technology is described in US 8,003,040 B2 (El-Siblani), which relates to a method for producing three-dimensional objects by solidifying layers in a pattern with co-stimulating electromagnetic radiation.
[0293] In particular, the so-called SLA or DLP 3D printing methods are found to be useful. Useful technology equipment is commercially available from companies such as 3Shape, Rapid Shape 3D Printing, Formlabs, Lithoz, Prodways 3D Printing, Stratasys, EnvisionTec 3D Printing, and the like.
[0294] The additive manufacturing apparatus operates at a specific radiation wavelength, which is typically in the range of 350nm to 500nm.
[0295] The additive manufacturing apparatus may also be characterized by the resolution that can be achieved. Suitable resolutions are typically in the range of 5µm to 100µm, or 10µm to 80µm, or 20µm to 60µm.
[0296] After the additive manufacturing process, the printed article can be post-processed if necessary.
[0297] Useful post-processing steps include cleaning and post-curing of the cleaned article.
[0298] Cleaning of the 3D printed article can be accomplished by using a cleaning solution and / or by performing a so-called spin cleaning method.
[0299] By performing the cleaning step, undesirable residues of the curable resin remaining on the surface of the 3D printed article can be removed.
[0300] Suitable cleaning solutions include alcohols, such as ethanol or isopropanol; esters of carboxylic acids, such as dibasic esters of carboxylic acids and / or tribasic esters of carboxylic acids; or mixtures thereof.
[0301] Suitable cleaning solutions are also described in WO 2018 / 222395 A1 (3M).
[0302] The spin cleaning method includes the step of moving or rotating the three-dimensional article. By doing so, mass inertia forces are generated.
[0303] The term "mass inertia force" referred to herein may be specified as force per unit mass and may therefore be m / s 2 In addition, the mass inertia force can be represented by the G force as a factor of the acceleration due to gravity. For the purposes of this text, the acceleration due to gravity is 9.81 m / s 2 So, for example, 9.81 m / s 2 The mass inertia force can be expressed as 1G.
[0304] Acceleration forces or mass inertia forces are caused by moving, for example rotating, an object.
[0305] The centrifugal force on a particle on the surface of a three-dimensional article generally depends on the rotation speed and the radius of the particle from the axis of rotation.
[0306] By varying parameters such as the speed of movement or rotation, the duration of movement or rotation and / or the axis of rotation, this technique allows adjusting the amount and layer thickness of the radiation curable composition remaining on the surface of the three-dimensional article.
[0307] In one embodiment, the mass inertia force generated in the cleaning step corresponds to a G-force of at least 100G. A mass inertia force of 100G has been shown to be suitable for removing moderately to highly viscous radiation-curable materials. One skilled in the art will recognize that the mass inertia force required for the cleaning step may be lower for less viscous materials and higher for more viscous materials. This approach is described, for example, in WO 2019 / 023120 A1 (3M).
[0308] Post-curing generally includes the step of applying heat or radiation to the 3D printed article. If desired, post-curing can be performed under reduced pressure.
[0309] Performing a post-curing step often helps to further enhance the mechanical properties of 3D printed parts.
[0310] The post-curing step can be characterized by the following features alone or in combination: application of radiation with a wavelength of 350 nm to 500 nm; application of a heating step of 30°C to 200°C or 40°C to 150°C.
[0311] Devices that can be used to post-cure three-dimensional articles obtained by additive manufacturing are commercially available, for example, from Rapidshape 3D Printing, Sanxuanpu, EnvisonTEC 3D Printing, ShapeLong, etc.
[0312] The present invention also relates to a cured composition or article obtainable by or capable of being obtained by curing the curable composition described herein.
[0313] The cured composition can generally be characterized by the following features, alone or in combination:
[0314] a. Opalescence OP: less than 15, measured on a sample with a thickness of 1.0 mm;
[0315] b. Flexural strength: 50MPa to 200MPa, measured according to ISO 4049 (2019);
[0316] c. E-modulus: 1 GPa to 4 GPa, determined according to DIN EN 843-2:2007.
[0317] Combinations of features a) and b); or a), b) and c) are sometimes preferred. If desired, the parameters can be determined as described in the Examples section.
[0318] Opalescence of less than 15% has been found to be suitable for providing a cured composition having the shape of, for example, an orthodontic article that is barely visible in a patient's mouth.
[0319] The flexural strength and / or E-modulus within the above ranges are found to meet physicians' expectations regarding mechanical properties for articles used in the orthodontic field.
[0320] The cured composition can have different shapes and sizes.
[0321] The cured composition typically includes a convex surface on one side and a concave surface on the other side.
[0322] Suitable shapes include orthodontic attachments, orthodontic brackets, buccal tubes, Class II and Class III aligners, buttons, splints, and other attachment devices, particularly orthodontic attachments.
[0323] The dimensions (x, y, z dimensions) of the cured composition or article are typically in the range of 0.5 mm to 10 mm for each dimension.
[0324] The curable composition is particularly useful for producing orthodontic attachments for so-called orthodontic therapy, which is a therapy or method for straightening the teeth in a patient's mouth.
[0325] This approach typically involves the following steps:
[0326] a. processing the curable composition in a laminar manufacturing process, optionally followed by post-processing steps, such as cleaning and curing, to obtain a 3d printed orthodontic attachment;
[0327] b. Insert the orthodontic attachment into the cavity of the tooth positioning tray;
[0328] c. Insert the dental positioning tray into the patient's mouth;
[0329] d. attaching orthodontic attachments to the surfaces of the teeth to be corrected;
[0330] e. Remove the dental positioning tray from the patient's mouth;
[0331] f. Optionally insert an orthodontic appliance tray that engages with an orthodontic attachment.
[0332] The attachment and / or fixation of orthodontic attachments to tooth surfaces may be supported by the use of dental adhesives. Suitable dental adhesives are commercially available, for example Scotchbond ™Universal (3M Oral Care). Suitable dental adhesives are also described in US 1 1 ,160,733 B2 (Thalacker et al.) or US 7,700,668 B2 (Thalacker et al.).
[0333] Alternatively, dental cement may be used. Suitable dental cements are commercially available, for example RelyX ™ Unicem (3M Oral Care Company) or RelyX ™ Universal (3M Oral Care Company). Suitable dental cements are also described in WO 2017 / 100231 A1 (3M) or US 8,236,871 B2 (Hecht et al.).
[0334] The present invention also relates to a kit comprising a tooth positioning tray and any of the following: at least one cured composition having the shape of an orthodontic attachment as described herein, or at least one curable composition as described herein, and optionally an orthodontic appliance tray.
[0335] Tooth positioning trays are commonly used to place orthodontic attachments onto a patient's teeth. Examples of tooth positioning trays and related methods are described in US 2015 / 0313687 A1 (Blees et al.), US 2020 / 131356 A1 (Zech et al.).
[0336] Orthodontic trays are used to straighten teeth like braces. They use gentle and constant force to move teeth into the desired position. They are usually clear and custom made.
[0337] The entire disclosure of the patents, patent documents and publications cited herein are incorporated by reference as a whole, as if each was incorporated separately. Various modifications and changes to the present invention will be apparent to those skilled in the art without departing from the scope and spirit of the present invention. The above specifications, examples and data provide a description of the manufacture and use of the compositions of the present invention and the methods of the present invention. The present invention is not limited to the embodiments disclosed herein. It will be appreciated by those skilled in the art that many alternative embodiments of the present invention may be prepared without departing from the spirit and scope of the present invention.
[0338] The following examples are given to illustrate the present invention.
[0339] Example
[0340] Unless otherwise stated, all parts and percentages are based on weight, all water is deionized water, and all molecular weights are weight average molecular weight. In addition, unless otherwise stated, all experiments were performed under ambient conditions (23°C; 1013 mbar).
[0341] method
[0342] Viscosity
[0343] If necessary, viscosity can be measured using a Physica MCR 301 (Anton Paar Germany GmbH, Ostfildern-Scharnhausen, Germany) at 23.0 °C with a flow rate of 0.1 s -1 With 1,000s -1 The shear rate between 20 and 25 mm was measured using a 25 mm plate / cone system.
[0344] transparency
[0345] If necessary, transparency can be determined with a spherical benchtop spectrophotometer Color i7800 (x-rite, Michigan USA). To measure transparency, a sample with a height of 1.0 mm and a diameter of 15 mm is placed between the sphere and the sensor with a specific transmission sample holder from x-rite. Measurement parameters: including mirror, mixing opening 10 mm, field of view 6 mm, wavelength between 360 nm and 780 nm, step size 10 nm. The transmittance TR [%] is the average of all transmittance values passing through the sample with a step size of 10 nm between 400 nm and 700 nm relative to the measurement without the sample in the beam.
[0346] Opalescence (OP)
[0347] If desired, opalescence can be measured using a spherical benchtop spectrophotometer, Color i7800 (X-Rite, Inc., Michigan, USA), using the above formula. Opalescence is measured using a sample having a height of 1.0 mm and a diameter of 15 mm.
[0348] Particle size distribution (non-nano sized particles)
[0349] If desired, particle size can be measured using a Malvern Mastersizer 2000 (Malvern Instruments, Malvern, Worcestershire, UK) light scattering instrument. The Mastersizer 2000 uses integrated optics to cover the range from 0.02 µm to 2000 µm. The mixture to be analyzed is added to a test chamber filled with isopropanol until an obscuration of approximately 8% to 15% is reached. In order not to change the particle size distribution, ultrasound is not applied. The raw data is processed with the instrument software, using a refractive index of 1.459 and applying a Mie correction and the Fraunhofer approximation, which are common techniques known to experts.
[0350] Particle size distribution (nano-sized particles)
[0351] The measurement of nanoparticle size is preferably based on the transmission electron microscopy (TEM) method, whereby the population is analyzed to obtain the average particle size. The preferred method for measuring particle size can be described as follows:
[0352] The approximately 80 nm thick sample was placed on a 200 mesh copper grid with a carbon stabilized polyvinyl acetate substrate (SPI Supplies-Structure Probe, Inc., West Chester, PA). Transmission electron micrographs (TEM) were taken at 200 KV using a JEOL 200CX (JEOL, Ltd., Akishima, Japan, and sold by JEOL USA, Inc.). The population size of approximately 50-100 particles can be measured and the average diameter determined.
[0353] Flexural Strength (FS)
[0354] If required, flexural strength measurements can be performed according to ISO 4049 (2019) using a universal testing machine (Zwick Z010, crosshead speed 1 mm / min) and specimens with dimensions of 2 mm × 2 mm × 25 mm. Flexural strength is usually given in MPa.
[0355] E-Modulus (EM)
[0356] If required, EM(I) can be determined according to ISO 4049 (2019) using a test bar with dimensions of 2 mm × 2 mm × 25 mm, where the width of the specimen is 6 mm. The E-modulus is determined in the range of 20% to 50% of the maximum force of the specimen. The E-modulus is given in [GPa].
[0357] Material
[0358] The following materials were used:
[0359]
[0360] Table 1
[0361] General method for producing surface treated discrete nanosized fillers
[0362] The sol containing nano-sized particles is mixed with the desired silane surface treatment agent and stirred under reflux in a solvent such as ethanol for several hours (e.g., 2 to 10 hours). If appropriate, the (meth)acrylate component or a portion thereof is added and the mixture is stirred again for several hours. The solvent is removed under reduced pressure.
[0363] General method for producing surface treated fumed silica
[0364] The fumed silica, silane and solvent were mixed with a stirrer for about 2 hours. The dispersion was dried in an oven at ambient temperature until the solvent evaporated. The dried fumed silica was sieved with a 500µm sieve. The final condensation of the silane on the surface of the fumed silica was carried out at above 100°C for 3 to 4 hours, followed by a final sieving of the silane-treated fumed silica with a 100µm sieve.
[0365] General method for producing curable compositions
[0366] The components were mixed using a high-speed mixer in the absence of light. The mixture was then evacuated in a laboratory kneader.
[0367] The following composition was produced:
[0368]
[0369] Table 2; CE: Comparative Example; IE: Inventive Example
[0370] General method for producing 3D printed products
[0371] Layer-by-layer manufacturing process :
[0372] The composition was poured into the working tray of a commercially available DLP printer (Rapidshape, Heimsheim, Germany). The pre-processed data (STL file; shape of a three-dimensional cuboid object; 25 mm × 2 mm × 2 mm) was loaded into the printer. The following printing conditions were applied: Curing light wavelength: 360 nm to 420 nm light; Curing light intensity: 5 W / m 2 Up to 100W / m 2 ; Exposure time: 1 s to 11 s; Layer thickness: 25 µm.
[0373] Three-dimensional products
[0374] The three-dimensional article can be produced as follows: the composition is placed in a barrel of a stacking manufacturing device. By using the above parameters in a stacking manufacturing process, the three-dimensional article is produced layer by layer. The three-dimensional article has the shape of an orthodontic article. The three-dimensional article is taken out from the barrel of the stacking manufacturing device.
[0375] Cleaning process :
[0376] The three-dimensional article may be cleaned in excess material as described in WO 2019 / 023120 A1 (3M) using the parameters described in the above text.
[0377] Post-curing steps
[0378] For final curing of three-dimensional products, a 50 mW / cm 2 Up to 500mW / cm 2 A light curing device emitting light between 360 nm and 420 nm. If necessary, light curing of the sample to complete cure can be carried out under reduced pressure (in the range of 1 mbar to 100 mbar).
[0379] The performance of the obtained samples was evaluated and the results are given in Table 3.
[0380]
[0381] Table 3
[0382] Figure 2 Pictures of samples CE1, CE2, IE1, IE2 and CE3 (from left to right) having the shape of orthodontic articles are shown in . The sample in the upper left corner corresponds to CE1 and the sample in the lower right corner corresponds to CE3.
[0383] Sample CE1 is opaque and contains nanocluster fillers and fumed silica.
[0384] However, sample CE2 contained discrete nanofiller particles with an average particle size of about 50 nm. The sample was milky white.
[0385] Sample CE3 is transparent and contains no filler.
[0386] Sample CE4 is opaque and contains fumed silica.
[0387] However, samples IE1 and IE2 (invention) contained discrete surface treated nanofiller particles with an average particle size ranging from 10 nm to 40 nm. The samples were transparent rather than milky.
[0388] Figure 3 Sample IE1 is shown attached to a tooth surface. Due to its transparency, the sample is barely visible on the tooth surface.
[0389] Use of the curable compositions described herein containing discrete filler nanoparticles enables the fabrication of small articles that are highly transparent and barely visible on tooth surfaces.
[0390] This is in contrast to formulations containing nanoclusters (CE1) or commercially available flowable composites.
[0391] Surprisingly, the clarity of the cured composition is even comparable to that of a formulation without any filler (CE3). Furthermore, the cured composition exhibits beneficial mechanical properties such as flexural strength (after storage in water for 24 hours).
Claims
1. A curable composition comprising a. (Meth)acrylates not containing a urethane moiety, b. Urethane (meth)acrylate, c. Photoinitiator, d. Discrete nano-sized filler particles, the discrete nano-sized filler particles having an average particle size in the range of 10 nm to 40 nm, The surface has been treated with a silane surface treatment agent selected from Silane surface treatment agents comprising a (meth)acrylate moiety, A silane surface treatment agent that does not contain a (meth)acrylate moiety, and A mixture of these, and The discrete nano-sized filler particles are present in an amount of 20 wt % or more, e. Additives, The curable composition does not contain filler particles other than those described above in an amount of 2 wt % or more each, and does not contain a polymerizable component containing only one (meth)acrylate moiety in an amount of 1 wt % or more, wt % relative to the curable composition.
2. The curable composition according to any one of the preceding claims, characterized by the following features alone or in combination: Viscosity: at 23°C, shear rate 1s -1 hour, ; Capable of being cured by radiation having a wavelength in the range of 350nm to 500nm.
3. The curable composition according to any one of the preceding claims, the photoinitiator having a light absorption peak in the range of 350 nm to 500 nm.
4. The curable composition according to any one of the preceding claims, wherein the discrete nano-sized filler particles are characterized by the following features, alone or in combination: comprising oxides of Si, Zr, Al, and mixtures thereof; having a particle size of 80 m 2 / g or more BET specific surface area.
5. The curable composition according to any one of the preceding claims, the surface treatment agent comprising a (meth)acrylate moiety being characterized by the formula: A m BSi(R 1 ) n (OR 2 ) 3-n wherein A comprises a (meth)acryloyl moiety, B comprises a spacer group, such as (i) a linear or branched C1 to C 12 Alkyl, (ii) C6 to C 12 aryl, (iii) an organic group having 2 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds, R 1 contains an alkyl group or an aryl group, and R 2 Contains an alkyl group, Where m=1, 2 or 3, and n=0, 1 or 2.
6. The curable composition according to any one of the preceding claims, the surface treatment agent not comprising a polymerizable moiety being characterized by the formula: DSi(R 1 ) n (OR 2 ) 3-n wherein D comprises (i) a linear or branched unsubstituted or substituted C1 to C 16 Alkyl, (ii) unsubstituted or substituted C6 to C 12 an aryl group, or (iii) an organic group having 2 to 20 carbon atoms bonded to one another via one or more ether, thioether, ester, thioester, thiocarbonyl, amide, carbamate, carbonyl and / or sulfonyl bonds, R 1 Contains C1 to C6 alkyl groups or C6 to C 12 an aryl group, and R 2 Contains a C1 to C6 alkyl group, And n=0, 1 or 2.
7. A curable composition according to any one of the preceding claims, the discrete nano-sized filler particles having been surface treated with a surface treatment agent comprising a (meth)acrylate moiety and a surface treatment agent not comprising a (meth)acrylate moiety, wherein preferably the surface treatment agent comprising a (meth)acrylate moiety is used in a higher amount by weight than the surface treatment agent not comprising a (meth)acrylate moiety.
8. A curable composition according to any one of the preceding claims, comprising the following amounts of the respective components: Methacrylates not containing urethane moieties: 20 to 75 wt %, Urethane (meth)acrylate: 5 to 25 wt %, Photoinitiator: 0.01 wt% to 5 wt%, Discrete surface treated nano-sized filler particles: 20% to 50% by weight, Additives: 0.001 wt % to 10 wt %; wt % relative to the curable composition.
9. The curable composition according to any one of the preceding claims, which does not comprise a polymerizable component comprising an acidic moiety, a plasticizer, each in an amount of 1 wt% or more, wt% relative to the curable composition.
10. A cured composition obtainable by curing a curable composition according to any one of the preceding claims, preferably by processing the curable composition in a laminate manufacturing process.
11. The cured composition of claim 10, characterized by the following features alone or in combination: Transparency: 60% to 85%, measured on a 1mm thick sample with a wavelength in the range of 400nm to 700nm; Opalescence: less than 15, measured on a sample 1 mm thick; Flexural strength: 50MPa to 200MPa, measured according to ISO 4049 (2019); E-modulus: 1 GPa to 4 GPa, determined according to DIN EN 843-2:2007.
12. The cured composition according to any one of claims 10 to 11, having the shape of an orthodontic attachment, in particular an orthodontic attachment, an orthodontic bracket, a buccal tube, a Class II and Class III corrector, a button or a splint.
13. A cured composition for use in a method for correcting teeth, the method comprising the steps of: attaching the cured composition according to any one of claims 10 to 12 to the surface of a tooth located in the patient's mouth by means of a tooth positioning tray, removing the tooth positioning tray, inserting an orthodontic appliance tray into the patient's mouth, the orthodontic appliance tray engaging the cured composition attached to the surfaces of the teeth, The cured composition Has the shape of an orthodontic attachment, Having a transparency in the range of 60% to 85% measured on a sample 1 mm thick with light having a wavelength in the range of 400 nm to 700 nm, has a flexural strength of 50 MPa to 200 MPa measured in accordance with ISO 4049 (2019), and The invention comprises: a (meth)acrylate free of urethane moieties, a urethane (meth)acrylate, and surface treated discrete nano-sized filler particles in an amount of 20 wt % to 50 wt %, based on the weight of the cured composition.
14. A method of producing an orthodontic attachment, the method comprising the step of processing a curable composition according to any one of claims 1 to 9 using a lamination manufacturing process.
15. A kit box, comprising: Tooth positioning trays; and at least one curable composition according to any one of claims 1 to 9; or at least one cured composition according to any one of claims 10 to 13; and optionally an orthodontic appliance tray.
Citation Information
Patent Citations
Urethane di(meth)acrylate derivatives of 1,3-bis(1-isocyanato-1-methylethyl)benzene
EP0934926A1
Radically curable urethane prepolymers and their use in dental materials
EP1242493B1
Dental adhesive composition, preparation and use thereof
US11160733B2
Mockup representing a dental arch including analogs approximating orthodontic brackets and method of making the mockup
US20150313687A1
Radiation curable composition for additive manufacturing processes
US20200131356A1